Tree diversity, use and carbon stocks in productive restoration areas in Calakmul, Campeche - Hernández-Dzib, Germán Alberto; Esparza-Olguín, Ligia; Martínez Romero, Eduardo; Pat-Fernández, Lucio; Maya-Martínez, Aixchel (Ecosistemas y Recursos Agropecuarios, 2021)
Tropical forests of the Calakmul Biosphere Reserve (REBICA) are home to high biodiversity and provide diverse ecosystem services threatened by the advance of the agricultural frontier. Productive restoration (RP), as a strategy that articulates the needs of producers and the conservation of natural resources, was implemented in modules in the ejidos Benito Juárez II (BJ), Eugenio Echeverría Castellot I (EEC) and Los Angeles (LA), adjacent to the REBICA. The objectives of this study were describe the RP strategies used and analyze the initial conditions of composition, structure, aerial biomass and carbon storage. The ejidos EEC and LA were associated with agroforestry systems, while in BJ a silvopastoral system was implemented, estimating densities of 1 718 ind ha-1, 2 885 ind ha-1 and 1 854 ind ha-1 respectively. True diversity (1D) ranged from 20.8 in LA to 15.13 in EEC and 13.47 in BJ. Sixteen potential uses were recognized for the identified species of which 47 were protected under CITES, IUCN and NOM-059 lists. The carbon values corresponded to 6.96 Mg C ha-1 in BJ, 10.32 Mg C ha-1 in EEC and 34.40 Mg C ha-1 in LA. The variations in composition, structure, biomass and carbon estimated indicate that the estimation of this baseline will facilitate the generation of a monitoring program that will allow evaluating the impact of the restoration actions implemented and, where appropriate, modifying them to accelerate the recovery of the analysed attributes.